Sensatezza del mondo e dimensione pratica del senso comune in Kant - Falduto, Antonino (Diciottesimo Secolo, 2025)
In contrast to the many studies that deal with Kant’s concept of common sense from an aesthetic point of view, I will rather focus on its practical meaning. In this way, my aim is to underline the dimension of commonalty of both taste and healthy human intellect. I will defend the thesis according to which the meaning of the adjective “common” in the expression “common sense” becomes clear only once the practical normativity of reason is emphasized. In order to show this, I will firstly focus on Kant’s third Critique, start from some terminological-conceptual distinctions expressed there, refer to the discussion on the commonalty of feeling, and take the “healthy” (i.e., sound) intellect into consideration. I will secondly turn to Kant’s Anthropology, in order to conclude my argument and highlight the practical, i.e., at the same time moral and political, significance of the yet uncultivated commonalty of sense and intellect.